2023
DOI: 10.3390/fermentation9060578
|View full text |Cite
|
Sign up to set email alerts
|

Development of Blood Sugar Regulatory Products from Momordica cochininensis via Probiotic Fermentation

Abstract: Type II diabetes is the most important health issue in the whole world. Besides the use of prescribed drugs to control blood glucose level, recently, the development of health supplements is being actively explored. Owing to its high nutritional value, Momordica cochinchinensis Spreng. (Gac) is potentially a good source for developing this supplement. In recent years, the aril of Gac has been utilized as a substrate for developing various forms of supplements, but the pulp has been neglected as a byproduct. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Firstly, GJ contains natural substrates and could present prebiotic compounds that support the growth of probiotic Lactobacilli . 15,26 Secondly, FGJ contains L. paracasei , which is used in the probiotic fermentation of the juice (8.38 log CFU mL −1 juice after fermentation) and may contribute to the observed highest Lactobacilli counts. Finally, FGJ contains metabolites produced from the fermentation by L. paracasei , such as lactic and acetic acids, which might further encourage the growth of probiotics like Lactobacilli while inhibiting other microorganisms during fecal fermentation.…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, GJ contains natural substrates and could present prebiotic compounds that support the growth of probiotic Lactobacilli . 15,26 Secondly, FGJ contains L. paracasei , which is used in the probiotic fermentation of the juice (8.38 log CFU mL −1 juice after fermentation) and may contribute to the observed highest Lactobacilli counts. Finally, FGJ contains metabolites produced from the fermentation by L. paracasei , such as lactic and acetic acids, which might further encourage the growth of probiotics like Lactobacilli while inhibiting other microorganisms during fecal fermentation.…”
Section: Resultsmentioning
confidence: 99%
“…( Nayak et al, 2010 ) found that fermented noni juice had hypoglycemic and hepatoprotective effects in diabetic rats, and speculated that it might be a substitute for glibenuride, an excellent hypoglycemic drug. ( Wu et al, 2023 , Li et al, 2014 ) fermented carrot juice with Lactobacillus plantarum , and the results showed that the strain promoted the production of short-chain fatty acids in the fermented juice, resulting in a higher proportion of short-chain fatty acid content. Chain fatty in the colon of rats with type II diabetes.…”
Section: Functional Activities Of Fermented Fruit and Vegetable Juicementioning
confidence: 99%
“…α-glucosidase and α-amylase are two important carbohydrate hydrolases, and inhibition of the activity of these two enzymes will reduce the production of free glucose, thereby regulating human blood sugar. ( Wu et al, 2023 ) screened lactic acid bacteria with hypoglycemic function and added them into apple juice for fermentation. The results showed that the inhibition ability of fermented apple juice on α-glucosidase was significantly higher than that of unfermented apple juice, which may be related to exopolysaccharides produced by lactic acid bacteria, which can interact with enzymes through electrostatic attraction or hydrogen bonding.…”
Section: Functional Activities Of Fermented Fruit and Vegetable Juicementioning
confidence: 99%